A signaling pathway AKTing up in schizophrenia - Arguello, P. Alexander (American Society for Clinical Investigation, 2008)
The serine/threonine protein kinase AKT (also known as PKB) signaling pathway has been associated with several human diseases, including schizophrenia. Studies in preclinical models have demonstrated that impaired AKT signaling affects neuronal connectivity and neuromodulation and have identified AKT as a key signaling intermediary downstream of dopamine (DA) receptor 2 (DRD2), the best-established target of antipsychotic drugs. A study by Tan et al. in this issue of the JCI strengthens links among AKT signaling, DA transmission, and cognition in healthy individuals and offers potential avenues to explore in an effort to find more effective pharmacotherapies for schizophrenia and related disorders (see the related article beginning on page 2200).